Prevalence of gastrointestinal helminth infections in free-range laying hens under mountain farming production conditions. Issue 6 (2nd November 2017) - Wuthijaree, K.; Lambertz, C.; Gauly, M.
ABSTRACT: 1. A cross-sectional study was conducted from September 2015 to July 2016 in South Tyrol, Northern Italy to examine the prevalence of gastrointestinal helminths in free-range laying hens under mountain farming production conditions. 2. A total of 280 laying hens from 14 free-range mountain farms (4 organic, 10 conventional) were randomly collected at the end of the laying period. Faecal samples were taken to analyse faecal egg counts (FEC) and faecal oocyst counts (FOC). The gastrointestinal tracts were removed post mortem and examined for the presence of helminths. 3. In faeces, FEC values averaged 258 eggs per g of faeces, which were dominated by Ascaridia galli and Heterakis gallinarum . Mean FOC was 80 oocysts/g. In the gastrointestinal tract, at least one nematode species was found in 99.3% of the examined hens. H. gallinarum was the most prevalent nematode (95.7%), followed by Capillaria spp. (66.8%) and A. galli (63.6%). Thirty per cent of the chickens were infected with cestodes (tapeworms). Correlation coefficients between worm counts of H. gallinarum, Capillaria spp. and A. galli ranged from 0.41 to 0.51. 5. The helminth prevalence did not differ between conventional and organic farms, whereas total worm burden was higher in organic compared with conventional farms (318.9 vs. 112.0). Prevalence and infection intensity did not differ between farms that used anthelmintic treatments and those that did not. 6. In conclusion, free-range laying hens under the studied mountain farming conditions are at high risk of nematode infection, especially in organic systems. The vast majority of hens are subclinical infected with at least one helminth species.